Pengelolaan Kelas dan Implikasinya Dalam Pembelajaran - Winda Ika Riyani (Prodi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah IAI Hamzanwadi NW Pancor, 2023)
Classroom management for students is a psychological activity that involves various components to create synergistic psychological activities and optimal functioning. Soul activity is based on the soul as power, especially in learning activities. The quality of learning with high concentration and attention as the main part of the perfection of students' understanding of teaching materials Classroom management is the teacher's skill in creating, controlling and maintaining optimal learning conditions. The essence of good and optimal classroom management is that problems that arise that can interfere with learning can be resolved through effective strategies. The second grade management objective is the general objective which is an effort to provide and utilize facilities to support teaching and learning activities. Classroom management requires principles that must be held by the teacher in managing the class, such as warmth and enthusiasm, challenge, variety, flexibility, emphasis on positive things, and instilling discipline. This is because in the classroom there are various types of children in the class, requiring varied teacher treatments in developing teaching methodologies as well as class management. Along with specific objectives, which are intended to guide students in improving their abilities and willingness to learn. The approach taken by the teacher in improving student learning in class. These approaches are 1) Power Approach. 2) Threat Approach, 3) Freedom Approach, 4) Recipe Approach, 5) Threat Approach. 5) Teaching Approach, 6) Behavioral Change Approach, 7) Socioeconomic Approach, 8) Work Approach Group, and 9) Eclectic and Pluralistic Approach. The implementation of the management of the teaching and learning process is a series of teacher activities starting from planning the teaching and learning process, organizing the teaching and learning process, supervising the teaching and learning process activities, and conducting evaluations and follow-up. Pengelolaan kelas bagi peserta didik merupakan aktivitas kejiwaan yang melibatkan berbagai komponen untuk menimbulkan aktivitas kejiwaan bersinergi dan berfungsi yang optimal. Aktivitas jiwa didasarkan pada jiwa sebagai power terutama dalam kegiatan belajar. Kualitas pembelajaran dengan konsentrasi dan perhatian yang tinggi sebagai bagian utama kesempurnaan pemahaman peserta peserta didik terhadap materi ajar Pengelolaan kelas adalah keterampilan guru dalam menciptakan, mengendalikan, dan memelihara kondisi belajar yang optimal. Inti dari pengelolaan kelas yang baik dan optimal, permasalahan yang muncul yang dapat mengganggu pembelajaran dapat teratasi lewat strategi yang efektif. Tujuan pengelolaan kelas dua yakni tujuan umum dimana ini adalah upaya menyediakan serta memanfaatkan fasilitas dalam menunjang kegiatan belajar mengajar. pengelolaan kelas diperlukan prinsip-prinsip yang harus dipegang oleh guru dalam mengatur kelas, Sperti hangat dan antusias, tantangan, bervariasi, keluesan, penakanan pada hal-hal posititf, dan penanaman disipilin. Hal ini dikarenakan dalam kelas terdapat berbagai tipe anak dalam kelas, menuntut adanya perlakuan-perlakuan guru yang variatif dalam mengembangkan metodologi pengajaran sekaligus pengelolaan kelasnya.Beserta tujuan khusus, yang dimaksudkan untuk membimbing peserta didik dalam meningkatkan kempuan dan kemauannya perihal belajar. Pendekatan yang dilakukan guru dalam meningkatkan belajar siswa dikelas. Pendekatan tersebut adalah 1) Pendekatan Kekuasaan.2) Pendekatan Ancaman, 3)Pendekatan Kebebasan, 4 ) Pendekatan resep, 5) Pendekatan Ancaman.5) Pendekatan Pengajaran,6) Pendekatan Perubahan tingkah laku, 7) Pendekatan Sosial ekonomi,8) Pendekatan Kerja Kelompok ,dan 9) Pendekatan Elektis dan Pluralistik. Implementasi pengelolaan proses belajar mengajar adalah serangkaian aktivitas guru mulai dari merencanakan proses belajar mengajar, mengorganisasikan proses belajar mengajar melaksaanakan, mengawasi kegiatan proses belajar mengajar, dan melakukan evaluasi serta tindak lanjut.